A framework for the implementation of the Sustainable Development Goals in university programmes. (25th May 2021) - Leal Filho, Walter; Frankenberger, Fernanda; Salvia, Amanda Lange; Azeiteiro, Ulisses; Alves, Fatima; Castro, Paula; Will, Markus; Platje, Joost; Lovren, Violeta Orlovic; Brandli, Luciana; Price, Elizabeth; Doni, Federica; et al.
Abstract: There is a perceived need to develop approaches, methods and tools that may help higher education institutions to systematically introduce the Sustainable Development Goals ( SDGs) into research and teaching as an intrinsic part of their programs. However, at present, there is a gap in the literature on the suitable means to do so. This paper addresses this gap by examining the many foci and commitments for and about the SDGs that are currently included in university programs. An overview of the SDGs' focus at universities was presented using a survey to gather qualitative and quantitative data. . Based on current trends and gaps, this paper identifies the need for a framework which may be of assistance in facilitating the inclusion of the SDGs as a whole, and individually targets in particular in the programs of institutions of higher education. The scientific contribution of this paper value lies in the fact that this is one of the first papers to tackle the need for a framework which caters to a more systematic introduction of the SDGs in university programs. The basis for the framework approach, here introduced, includes institutional, thematic, structural and personal/individual aspects which need to be considered for proper implementation of the SDGs at the university level.